Playful public spaces - Riikonen, Juho-Atte (2015)
In the end phases of an urban design course that was oriented towards children, it dawned on me: the shocking realization that we are talking about play as something that is only significant for children. How could it be that we are talking about playgrounds that adults have no business in. Not that children don’t require specific attention, seeing that they are the future of our world, but what I experienced was quite the epiphany. I started wondering why playfulness isn’t discussed in our studies as a quality? Why isn’t play an important activity of adult life? Personally, all I do in my free time is play. I do all the things I don’t like doing for the sake of play. I play board games, computer games, football. I am exremely playful when I hang out with my friends as I joke around and talk about unserious matters. When I walk in the city I play with it. I do not walk for health reasons, I walk because I like walking for walking’s sake. I watch people for watching’s sake and I have coffee for the sake of a nice conversation. Such a big part of our lives deserves some attention, I thought. I started looking into urban design studies and found almost none that brought up play. As I was reading more, cities started looking alarmingly similar and serious. Public spaces, the areas in our cities that have the potential to be the adult playgrounds, began to feel more and more deserted. Slowly, I got increasingly convinced that play as a subject was worth studying. However, it quickly seemed like a difficult angle to approach public space design. Its definition was tricky and people I talked to associated it with children at the first chance. Regardless, in hopes of gaining a fresh perspective, something I felt the field of urban design sorely needed, I foolishly pushed onwards. The result is a short introduction to playful urban design – a merger between playtheory and urban studies.